Smart Campus: An Implementation of a Cloud-Based Mobile Learning Application - Boyinbode, Olutayo (Journal of Information, 2018)
A cloud-based mobile learning application allows access to learning resources stored in the cloud. The limitations of the traditional mobile learning such as insufficient storage, limited power have made mobile learning applications inefficient, hence the need to integrate mobile learning with cloud computing. This paper focuses on providing a smart platform where instructors or lecturers can upload learning resources to the cloud, and learners can access these resources with their mobile devices, after they have been successfully uploaded. Also the concepts, technologies, and tools used for the implementation were also discussed.